Purvi Mehta-Bhatt on nutrition insecurity and weather shocks in South Asia - Mehta-Bhatt, Purvi (International Food Policy Research Institute, 2014)
Parallel Sessions 9: Improving Resilience to Shocks in Regional Contexts. Purvi Mehta-Bhatt, Regional Representative, South Asia, International Livestock Research Institute (ILRI), India, Chair of Parallel Session 9D on "Building Resilience to Nutrition Insecurity and Weather Shocks in South Asia." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info